The Management of Marketing Changes and The Impact on The Success of Thailand Shopping Centers - Sophan, Piyatida; Thitilak, Thatchakon (Journal of Ecohumanism, 2024)
This research analyzes the issues and impacts of market changes on Thai shopping mall businesses in the digital era. It considers the effects of key factors, including consumer behavior, technology, energy costs, and organizational structure. The study employs qualitative research methods, conducting in-depth interviews with key stakeholders such as senior executives of shopping malls, business operators, and academics. The collected data is then analyzed to summarize key points and review literature on marketing strategies, organizational management, and transformational leadership. The findings reveal that the 4P marketing strategy remains a crucial framework but needs to be adjusted to align with the evolving impacts. Market changes affect Thai shopping mall businesses, prompting them to adapt, develop strategies, and integrate technology to enhance service delivery, create positive customer experiences, increase business opportunities, develop new business models, increase revenue, and expand their customer base. This strategic adjustment leads to the development of employee capabilities and the role of leaders in organizational transformation to meet market demands and achieve competitive advantage. Adapting and restructuring the organization to fit current and future market and societal needs require a holistic transformation approach or Systematic Transformation, which includes Market Transformation, Leadership Transformation, Organization Transformation, and Ecosystem Transformation, all of which are interrelated. This holistic transformation approach will drive the digital transformation of organizations and foster sustainable growth in the digital era.